A Improvement of efficiency in Tanjung Marolan farmers harvest process with thresher technology - Harahap, Agus Salim; Nababan, Esther Sorta Mauli; Siahaan, Nelson Manumpak Siahaan; Ziliwu, Meyman Sokhi (Talenta Publisher, 2019)
Human power which is relied on every harvest season becomes a big concern for farmers. Farmers in Ajibaho Village, Dusun VII Tanjung Marolan still utilize a simple equipment with human power to harvest rice. Some processes of harvest require longer time. It is started from cutting rice stalks, collecting rice stalks, and threshing rice by hitting it on a drum to thresh the rice from the stalks. After that, the rice was collected, put into white sack, and delivered to houses. This condition also depends on the weather which becomes longer when it is rain or sunny. A simple technology which uses thresher can be a good solution to achieve an efficiency of harvest process specially for the threshing process. The application of thresher machine is able to give a positive impact to increase harvest, to decrease daily cost, and to effectuate harvest process